Canada : Financial Sector Assessment Program-Technical Note-Stress Testing and Financial Stability Analysis. (IMF Staff Country Reports; Country Report, 2020)
This paper on Financial Safety Net and Crisis Management for the Canada reviews the stress testing and financial stability analysis. The paper highlights that the financial system's performance has been strong. The insurance sector has remained financially sound even in the low interest rate environment. Major banks, life insurers, and pension funds have expanded their footprints abroad. Canada has strong financial linkages with the United States. Macrofinancial vulnerabilities-notably, elevated household indebtedness and housing market imbalances-remain substantial, posing financial stability concerns. Major deposit-taking institutions would be able to manage severe macrofinancial shocks; however, mortgage insurers would probably need additional capital. Major deposit-taking institutions also hold enough liquidity buffers to withstand sizeable funding outflows. However, increased balance sheet complexity and reliance on wholesale and foreign exchange funding, and the extensive use of derivatives are some areas of concern that would warrant closer monitoring by the competent authorities and a more comprehensive quality assurance in the context of supervisory or macroprudential stress testing exercise.